PENGARUH KUALITAS PELAYANAN DAN KUALITAS HARGA PRODUK TERHADAP KEPUASAN KONSUMEN DI AYAM GEPREK MASBOY (Studi Akasus konsumen Ayam Geprek Masboy Daerah Sukarame) - edwar fadhoil; Abdul Fajar Iswara; Dwi Taufik Aziz; Vicky F.Sanjaya (Lampung Selatan: Sekolah Tinggi Ilmu Ekonomi Muhammadiyah Kalianda, 2023)
This study aims to determine: a. Effect of service quality on consumer satisfaction b. Effect of product quality on consumer satisfaction. The population in this study is allstudents or the public who have bought Geprek Mas Boy in the Sukarame area. Retrieval techniquesample using purvosive sampling, data obtained by distributing linksquestionnaire to social media (whatsapp, instagram, line) with a total of 52 respondent. The data analysis technique in this study is descriptive analysis.Data processing techniques using the SmartPLS 3 application. Research resultsshows that: a. Service quality has a positive and significant effect on consumer satisfaction for chicken geprek mas boy in the Sukarame area b. Price quality has a positive and significant effect on consumer satisfaction for chicken geprek mas boy in the Sukarame area. Keywords: service quality, product quality, customer satisfaction